Rancang Bangun Sistem Autentikasi Hotspot Berbasis Radius Server Menggunakan Mikrotik Pada Sekolah Menengah Kejuruan Negeri 5 Luwu - Rahmi Ningsy Guncya; Dasril Dasril; Muhlis Muhallim (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to design and build a hotspot network system using userman and proxy server radius at SMK Negeri 5 Luwu to solve problems because users are not limited in using devices to make internet connections in the school environment. Radius servers run a centralized user administration system. This system will certainly simplify the task of an administrator. With this system, users can use hotspots in different places by authenticating to the radius server. This research was conducted at SMK Negeri 5 Luwu. The research method used in this study is Network Development Life Cycle (NDLC). Data collection methods consisting of direct observation methods to the research location, interviews with one of the operators as well as network operators / administrators in the school, literature studies. Testing was conducted using browser, CMD and Speedtest. The results of research with the hotspto using userman and radius server using the same user as the password in user authentication management to improve network security have been successfully implemented internet networks in schools to improve network security, so it is very helpful for network providers in managing and monitoring all users connected to their networks.